Bulbul malika - Mian naveed nasir (Ferozsons (Pvt) Limited ; Lahore, 2000)
"Bulbul Malika" is a captivating tale of beauty, grace, and inner strength, portraying the journey of a woman who rises above challenges to find her voice and embrace her true identity, blending love and empowerment.